The Regularization of Zimbabwean Migrants: a Case of Permanent Temporariness - Carciotto, Sergio (African Human Mobility Review, 2021)
Since the early 2000s there has been a proliferation of policy initiatives in high income countries to attract highly skilled migrants who are perceived to be net contributors to host societies. Generally, highly skilled migrants enjoy numerous socio-economic opportunities and benefit from fast-track procedures to switch from temporary visas to permanent residency. South Africa has sought to capitalize on this trend through domestic legislation and policy that promotes economic growth by facilitating the admission of highly skilled workers. However, these measures have also prevented low-skilled workers from applying for permanent residency, irrespective of their length of time in the country. These policies beg the question whether it is morally acceptable for a liberal democracy to deny a pathway to permanent residency based on skill level. The paper draws on Joseph H. Carensâ€™ theory of citizenship and the principle that â€œthe longer one stays in a society, the stronger oneâ€™s claim to remain.â€ It uses the example of the Dispensation for Zimbabwean Project, a large regularization programme for temporary workers introduced in South Africa in 2010 to argue that temporary status should not be â€œpermanent,â€ but should lead to permanent residency after a period of time.